Interfacial electronic and vacancy defect engineering coupling of the Z-scheme CsSnBr3/SnS2 heterostructure for photovoltaic performance: a hybrid DFT study. Issue 9 (14th February 2023) - Zhang, Minjie; Lin, Yanming; Li, Jiayi; Wei, Xinru; Peng, Ying; Wang, Zhengkun; Maheskumar, V.; Jiang, Zhenyi; Du, Aijun
Abstract : Interfacial coupling of Z-scheme CsSnBr3 /SnS2 heterostructure induces a narrowing band gap and reduces carrier recombination rate. Coupling interface and Br vacancy defects of CsSnBr3 has excellent photovoltaic performance. Abstract : The photoelectric conversion efficiency of CsSnBr3 solar cells only reached 3.04% due to the insufficient separation of photogenerated charge and the short lifetime of the carriers. Herein, interfacial electronic properties and photovoltaic performance of the CsSnBr3 /SnS2 heterostructure without and with Bromine vacancy defects are studied using a hybrid density functional method. We find that strong coupling and hybridization of interfacial electronic states in the CsSnBr3 /SnS2 heterostructure can lead to a narrowing band gap, which induces excellent optical absorption. Bromine vacancies are introduced into the CsSnBr3 /SnS2 heterostructure to provide more electrons and modulate its physicochemical properties. Excitingly, the charge transfer forms a stronger built-in electric field in the VBr -CsSnBr3 /SnS2 heterostructure, which can effectively promote the charge transfer between VBr -CsSnBr3 (001) and the SnS2 monolayer complying with a Z-scheme pathway. The coupling interface and vacancy defects improve the photovoltaic performance of CsSnBr3 . This study offers a novel design idea for CsSnBr3 -based perovskite materials in photovoltaic applications.